Managing tertiary education institutions with excellence: An experience in balancing quality against profits - Yaacob, Mashkuri (2016)
Managing a University with the focus of achieving all round excellence is not an easy exercise, whether the University is public funded or privately funded. This talk attempts to highlight the speaker’s experience in managing a private University in Malaysia owned by the largest electricity utility provider in the country. The two major considerations are: 1. Can the University offer programs in the professional disciplines and hence produce excellent graduates for the respective industries? 2. Can the quest for excellence be sustained without incurring high costs and achieve high financial returns?